Teaching of new sport skill to weightlifters: problem in performance and motor learning - Kordi, H.; Mohamadi, J.; Ghotbi, M. (Journal of Human Sport & Exercise, 2013)
This study would report about one of the problems (learning of a new sport skill) that occurs probably following weightlifting and decrease range of motion (ROM). Weightlifters (WLs) group (n=20) and Non-Weightlifters (NWs) group (n=20) were trained overhand serve volleyball based on a similar schedule program. The Results of performance accuracy showed, WLs didn`t learn the skill, but NWs learned did. When ROM had been controlled, performance of WLs and NWs were not different. We observed, WLs had noticeable differences in pattern of joints displacement in comparison with NWs and reference pattern of serve skill. Thus, it seems that WLs encounter with some problems regarding performance and learning of new motor skills due to ROM`s limitation.